Impact of alley cropping system on soil fertility - Ferdush, Jannatul; Meftahul Karim, Md.; Jahan Noor, Iffat; Afrin Sadia Afrin Ju, Sadia; Ahamed, Tofayel; Sataya Ranjan Saha, Dr. (International Journal of Advanced Geosciences, 2019)
A field experiment was conducted to investigate the effect of pruned materials of two hedgerow species on wheat production and soil nutrient changes at different nitrogen levels in the research farm of the Bangabandhu Shiekh Mujibur Rahman Agricultural University (BSMARU) during November 2012 to March 2013. The design of the experiment was split plot, where two multipurpose tree species (MPTS) namely Gliricidia sepium and Leucaena leucocephala were arranged in main plots and five different doses of nitrogen (0, 25, 50, 75 and 100 % of recommended dose) with pruned materials were distributed to sub plots. Alley widths of both tree species were 6.0 meter. There were also control plots where full dose of recommended nitrogen was applied but no pruned material (PM) was incorporated. The soil chemical properties in the alleys consisting of G. sepium and L. leucocephala responded differently. Positive changes in the soil fertility in terms of soil pH, organic C, total N, available P, available S and exchangeable Ca, Mg, K and CEC of the top soil layer were observed in alley cropping system. Pruned materials application substantially reduced the nitrogen requirement for wheat production and 50 % Nitrogen fertilizer could be saved through pruned materials application. Among the tree species G. sepium seemed to be superior over L. leucocephala in building soil health.